A Randomized, Double-Blind, Placebo-Controlled Trial of Metformin Treatment of Weight Gain Associated With Initiation of Atypical Antipsychotic Therapy in Children and Adolescents - Klein, David J.; Cottingham, Elizabeth M.; Sorter, Michael; Barton, Bruce A.; Morrison, John A. (The American journal of psychiatry, 2006)
Objective: Second-generation, or atypical, antipsychotics effectively treat psychiatric illness in children and adolescents. However, weight gain and abnormalities in insulin sensitivity, including diabetes, complicate this therapy. Method: A 16-week double-blind, placebo-controlled trial was conducted to evaluate the effectiveness of metformin in managing weight gain in 39 subjects, ages 10-17, whose weight had increased by more than 10% during less than 1 year of olanzapine, risperidone, or quetiapine therapy. Body weight, body mass index (kilograms per square meter of height), and waist circumference were measured regularly, as were fasting insulin and glucose levels. Results: Weight was stabilized in subjects receiving metformin, while those receiving placebo continued to gain weight (0.31 kg week). Because the study was conducted with growing children, metformin treatment resulted in reduction in z scores for both weight and body mass index. The homeostasis model assessment, a surrogate indicator of insulin sensitivity, decreased in treated subjects. Overt diabetes was diagnosed in two subjects before treatment (elevated baseline fasting glucose and insulin values) and in two placebo-treated subjects (one at week 12 and the other after study completion). One subject taking placebo developed impaired fasting glucose. Placebo treatment was associated with the need to perform oral glucose tolerance testing upon study completion, by which three additional subjects were identified with impaired glucose tolerance. No serious adverse events resulted from metformin treatment. Conclusions: Metformin therapy is safe and effective in abrogating weight gain, decreased insulin sensitivity, and abnormal glucose metabolism resulting from treatment of children and adolescents with atypicals.